2021
DOI: 10.1186/s12877-021-02239-1
|View full text |Cite
|
Sign up to set email alerts
|

Associations between nut intake, cognitive function and non‐alcoholic fatty liver disease (NAFLD) in older adults in the United States: NHANES 2011-14

Abstract: Background Nuts are nutrient-rich and reported to provide some cognitive and cardiometabolic health benefits, but limited studies have focused on older adults. This study investigated the cross-sectional relationship between habitual nut intake, dietary pattern and quality, cognition and non-alcoholic fatty liver disease (NAFLD) in older adults. Methods Older adults (≥ 60 years) from the NHANES 2011-12 and 2013-14 cohorts, who had complete data on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 58 publications
(70 reference statements)
1
12
0
Order By: Relevance
“…Similar to our findings, Motamed et al. ( 42 ) found that WC presented excellent performance in the diagnosis of NAFLD(AUC: 0.8533, 95%CI: 0.8419-0.8646)and almost the same predictive power as fatty liver index (FLI), a widely used index for the diagnosis and evaluation of fatty liver development in a number of studies ( 43 , 44 ).…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our findings, Motamed et al. ( 42 ) found that WC presented excellent performance in the diagnosis of NAFLD(AUC: 0.8533, 95%CI: 0.8419-0.8646)and almost the same predictive power as fatty liver index (FLI), a widely used index for the diagnosis and evaluation of fatty liver development in a number of studies ( 43 , 44 ).…”
Section: Discussionsupporting
confidence: 91%
“…The health benefits of nuts appear to be dose dependent, which is often expressed as benefit per unit increase in the amount of nuts ( 50–52 ) or increasing frequency ( 53 , 54 ) of nut consumption. However, there was also indication that the dose-dependent relation may be curvilinear, where the maximum benefit of nuts is achieved at a certain threshold of nut intake ( 47 ). This is an important consideration as understanding the optimal amount that promotes health benefits will guide the development of specific dietary recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…In nutrition epidemiology, the associations between nut intake and various health outcomes rely on how nut and seed intake is categorized and compared. In previous studies, nut intake has been categorized in a number of ways: 1 ) binary classification of intake as nonconsumers compared with consumers defined as nut intake of ≥¼ ounce (or 7.1 g/d) ( 61 , 101 ), 2 ) based on per unit increments of half ( 47 ) or a serving (1 ounce or 28.5 g/d) ( 102 ), 3 ) based on current nut recommendations of 30 g/d ( 8 , 9 ), 4 ) per 50 g/d increment ( 53 ), and 5 ) in nut intake quantiles, e.g. tertiles ( 103 ) or quartiles ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nuts are nutrient-dense foods containing salutary compounds, including unsaturated fatty acids, vegetable protein, fiber, phytosterols, vitamins, minerals, and phenols [ 7 , 8 ]. They have been found to have beneficial effects on cardiovascular diseases (CVDs), obesity, cancers, and nonalcoholic fatty liver disease in epidemiologic studies and clinical trials [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Emerging evidence suggests that they may work by reducing oxidative stress and inflammation and improving vascular reactivity, insulin resistance, and lipid metabolism disorder [ 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%